An experimental platform of variable speed pumped storage unit under wave disturbance: introduction and preliminary progress. Issue 1 (June 2021) - Yang, Weijia; Yang, Jiandong; Zeng, Wei; Zhao, Zhigao; Zheng, Guiqiao; Peng, Tao; Huang, Yifan; Hu, Jinhong; Zeng, Zhenyu; Yang, Jiebin; Wang, Xuewu; Chen, Man
Abstract: The importance of pumped storage plants (PSPs) is continuously increasing in power systems with more and more variable renewable energies. For the research and development of PSPs, variable speed technology and sea-water PSP are two important new orientations. In this paper, an experimental platform of variable speed pumped storage unit under wave disturbance is introduced. The purpose of the platform is to study the design and operation mechanism of variable speed PSP based on various common technical problems, especially for the four aspects: transient processes, variable speed unit, coordination control, wave disturbance. The platform adopts a Chinese sea-water PSP in feasibility stage as the prototype, and a model scale of 1:4 is applied. It consists of nine sub-systems, including waterway system, variable speed reversible model unit, circulating water system, speed governor system, AC excitation and electric protection, coordination control, monitoring system, intelligent AC load and measurement system. The model unit contains a reversible pump turbine, a doubly fed induction machine, etc. The speed variation range is ±8%, and the rated power is 78.13 kW. The model runner meets the IEC standard with a reference diameter of 284.3 mm. The upstream water tank is a closed pressure tank that can adjust the pressure and discharge. The downstream water tank is an open water tank that can simulate wave level fluctuation. Regarding the control system, it has four core parts: local control unit, speed governor, converter and coordination controller. The experimental study content contains three key aspects: (1) performance validation for variable speed unit; (2) operating stability under complex disturbances; (3) capability of variable speed PSP during transient processes. The experimental study based on the platform aims for laying a theoretical and technical foundation for the follow-up construction and operation of real sea-water PSPs with variable speed units.